First use of antineoplastic agents in women with breast cancer in the state of Rio de Janeiro, Brazil - Santos, Ranailla Lima Bandeira dos; Osorio-de-Castro, Claudia Garcia Serpa; Sobreira-da-Silva, Mario Jorge; Pepe, Vera Lúcia Edais (Frontiers in Pharmacology, 2023)
CONTEXT: Breast cancer is the most common cancer, except for non-melanoma skin cancer, among women in Brazil and worldwide. Breast cancer treatment involves surgery, radiotherapy and chemotherapy, which is used in 70% of patients. This study analyzes the utilization of antineoplastic agents among women undergoing their first round of chemotherapy in Brazil's public health system (SUS) in the state of Rio de Janeiro. METHODS: Data from the SUS Outpatient Information System´s authorizations for high-complexity outpatient procedures (APACs) billed between January 2013 and December 2019 were extracted, and three datasets were created: all type 1 and type 2 APACs (including all chemotherapy procedures performed); all type 1 APACs; and first type 1 APACs (containing data only for the first round of breast cancer chemotherapy). Names of antineoplastic agents were standardized to enable the subsequent classification of therapy regimens, mitigating limitations related to data quality. Absolute and relative frequencies were used to describe sociodemographic, clinical and treatment characteristics, therapy regimen and supportive drugs. RESULTS: We analyzed 23,232 records of women undergoing their first round of chemotherapy. There was a progressive increase in the number of procedures over time. Women were predominantly white, lived in the capital and close to the treatment center. Most had stage 3 cancer at diagnosis (50.51%) and a significant proportion had regional lymph node invasion (37.9%). The most commonly used chemotherapy regimens were TAC (docetaxel, doxorubicine, cyclophosphamide) (21.05%) and AC (doxorubicin and cyclophosphamide) (17.71%), followed by tamoxifen (15.65%) and anastrozole (12.94%). Supportive drugs were prescribed to 386 women and zoledronic acid was predominant (59.58%). CONCLUSIONS: The findings point to important bottlenecks and possible inequities in access to treatment and medicine utilization for breast cancer patients in Brazil. Efforts to improve breast cancer treatment and prevention should not only focus on interventions at the individual level but address the disease as a public health problem. The study focused on women undergoing their first round of treatment, providing valuable insight into patient and treatment characteristics to inform policy decisions.